2023
DOI: 10.13187/me.2023.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Reputation and Innovation in the Higher Education Industry: A Correlation Study based on the RepTrakTM Model in the Context of Corporate Communication

Abstract: Although there is ample literature in organisational innovation, not enough attention is accorded to the correlation between innovation and corporate reputation in the context of corporate communication in the higher education industry. This study was prompted by the urge to close this research gap. Three hundred and thirty-one (331) international, or foreign students from the Infrastructure University of Kuala Lumpur (IUKL), Malaysia were recruited as respondents through a simple random sampling technique who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The relationship between leadership and organisational reputation has been the subject of extensive research (Avolio et al, 2004;Bass, & Riggio, 2006;Gusau et al, 2022Gusau et al, , 2023. Understanding how leadership qualities and behaviours affects organisational reputation is crucial for organisations seeking to enhance their image and build stakeholder trust.…”
Section: Relationship Between Organisational Leadership and Reputationmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between leadership and organisational reputation has been the subject of extensive research (Avolio et al, 2004;Bass, & Riggio, 2006;Gusau et al, 2022Gusau et al, , 2023. Understanding how leadership qualities and behaviours affects organisational reputation is crucial for organisations seeking to enhance their image and build stakeholder trust.…”
Section: Relationship Between Organisational Leadership and Reputationmentioning
confidence: 99%
“…The association between ethical leadership and organisational reputation has been consistently supported in research as shown in previously. By promoting ethical leadership, organisations can enhance their reputation, build stakeholder trust, and foster sustainable success (Gusau et al, 2022(Gusau et al, , 2023.…”
Section: B Ethical Leadership and Reputationmentioning
confidence: 99%
See 1 more Smart Citation